Pengembangan Kreativitas Melalui Alat Permainan Edukatif Anak Usia Dini - Muzdhalifah, Muzdhalifah (Pusat Studi Pendidikan Kreatifitas Anak Wadas Kelir Purwokerto, 2019)
Educational game tools (APE) are used as a means or media to play by children whichcontains educational values and can develop children's potential, one of which ispotential in creativity. This writing has the aim that children have creativity with thecreativity of children can train their motoric, practice concentration, socialization withfriends and the environment increases, fostering a spirit of leadership, and a highsense of trust. The approach in this study is a qualitative approach with data collectionmethods to see from the results of previous studies then analyzed. The importance ofeducational games for one's development will not be separated from the benefits ofthe game itself, both personally and for others. Educative media is used as analternative learning media for PAUD educators in changing conventional learningmethods into learning game or game simulation, so that it can be concluded from theresults of this study that educational games have elements of challenge, accuracy,reasoning or ethics in early childhood and from Educative media are children'screativity to develop. And from the results of previous studies also have such resultsthat the creativity of children develops when given educational games in whicheducational games are given to children adjusted to the age of the child.